ChemInform Abstract: Reactivity and Applications of Layered Silicates and Layered Double Hydroxides. Issue 37 (16th September 2014) - Selvam, Thangaraj; Inayat, Alexandra; Schwieger, Wilhelm
Abstract Review: 246 refs.